JeHe’s competence-based learning methodology in physics and mathematics - Herrera Castrillo, Cliffor Jerry (2025)
Introduction: Currently in universities worldwide, many efforts are being developed to reach a competency-based approach, for student learning, with the use of technology as a dynamizing and enhancing element of learning. With this project on the JeHe methodology, we want to contribute for students to achieve generic and specific competencies that will be of help for their professional development, thus evidencing a significant learning. Objective: To implement a Methodology for Competency-Based Learning of Mathematical Equations in Physics with the help of Technology in the Physics-Mathematics program. Method: 75 students, 6 teachers and 1 career coordinator, all from UNAN - Managua / CUR - Estelí, participated in the research. A mixed approach was considered, using theoretical, empirical and statistical methods. The research scenario was the implementation of JeHe’s Methodology for Competency-Based Learning, which provides theoretical bases and analyzes its effect on higher education.